Symposium 9: Conceptual Design, Extended Action Research, Team Building and Virtual Learning Environments: Symposium Introduction - Schrittesser, Ilse (Proceedings of the International Conference on Networked Learning, 2006)
The research questions and desiderata we would like to discuss at our symposium all converge in one central research interest: in how far and under which conditions can groups and teams represent an added value in the specific learning processes involved in higher education. Due to the academic fields we work in, our primary interest lies in learning processes which deal with professionalisation and/or with the training for professional job practice and which combine virtual learning environments along with co-present didactic settings. In this context we look for appropriate didactic "architectures" that are targeted at enhancing individual and group learning and personal growth. Specifically, we take a closer look at the potential co-present and virtual communities might develop when processes of professionalisation including personal growth are concerned. The first paper by Sylvia Logar, Ilse Schrittesser and Barbara Wenninger, entitled "Professional Communities - Potentials and Limits of Blended Learning Scenarios" deals with a research project on the assumed potential of self-reflective groups called "Professional Communities" for educating and training future academic professionals. The learning environment developed in the context of this research project is meant to specifically draw on the different qualities of face-to-face and on-line communicative structures in order to bring together researchers, students, experts and practitioners in a process of learning from each other and drawing on each other’s knowledge. In this context a research design is about to be developed that should facilitate the comparative observation and documentation of co-present and on-line group experiences and processes. The second paper by Renate Motschnig-Pitrik dealing with "The Effects of a Blended Course including Person Centred on Students’ Learning, Relationships and Teamwork" focuses on how courses in business informatics can shift their emphasis from primarily conveying subject knowledge to including and developing attitudes and skills as the basis for knowledge development. The author presents and evaluates a blended learning setting that relies on the theory of the American psychologist Carl Rogers and his definition of the Person Centered Encounter Group. The hypothesis is put forward and discussed that Encounter Groups can become highly efficient learning environments in an academic context when it comes to include more than just the cognitive dimension in the learning process. Moreover, it is shown that employing new media in the described scenario has an enhancing effect on group communication and group learning. The third paper by Kathrin Figl, Renate Motschnig-Pitrik and Michael Derntl on "Team and Community Building of Students of Business Informatics: Influence Factors in Blended Environments" elaborates on the ability to work in teams as a major success factor in the job field of business informatics. Consequently, the question is discussed how this ability can be established as a major learning outcome in the curriculum of business informatics on the basis of blended learning environments. The fourth paper by Renate Motschnig-Pitrik, Michael Derntl, Kathrin Figl, Sylvana Kroop, Sylvia Logar, Juergen Mangler and Barbara Wenninger deals with "Processes and their Support in a Developing Interdisciplinary Learning Community". This paper describes the creation of a scientific learning community in the context of a blended learning course. The different potentials of face-to-face communication versus on-line forms of interaction (e.g. on-line forums, on-line collaborative reading and writing etc.) for the formation of al learning community are analyzed. Participants report on their experiences concerning the added value of combining co-presence with web technology. Besides the blended learning design, also the interdisciplinary approach - educational scientists work along with computer and translational scientists - is qualified to promote the learning process. Finally, participatory action research is presented to have proved highly valuable for tracing the development of the community and for making the participants aware of when "learning about learning" has occurred.